Efficacy of Pulse Therapy of Oral Fluconazole in the Treatment of Seborrheic Dermatitis - Khondker, LI; Wahab, MA; Khan, MSI (Medicine Today, 2013)
An interventional study was carried out for a period of total two years in the department of Dermatology and Venereology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. Total sixty five patients of seborrheic dermatitis were selected and were treated with oral fluconazole 150mg in a single dose per week for 4 weeks. Follow up were done at the end of 4th week and 8th week. Among the patients, 31-45 years age group was highest 44%, highest 54% males and 21 (32%) had positive family history and 44 (68%) had negative family history of seborrheic dermatitis. Among the sixty five patients, mild form was 54%, moderate was 22% and severe was 12%. Highest patients of seborrheic dermatitis 51% had the duration of lesion 1 to 3 years and next 38% had the duration 4 to 6 years. Regarding site of lesions, maximum patients of seborrheic dermatitis 92% had involvement of scalp; next 46% had involvement in the eyebrow. The study showed that the response was very good in 31.5 of cases, good response was found in 24.5% of cases, fair in 26% of cases and poor response was observed in 18.5% of cases. The study showed that 83% of study population was seen without clinical side-effect and only 17% were seen with side-effect(anorexia and dydpepsia) and it was showed that very good improvement 35% observed on the 1st follow up visit at the fourth week, 30% had good, 15% fair and poor improvement 20% respectively. On the 2nd follow up visit at the end of eight week, very good improvement was 39% cases; good, fair and poor improvement was 26%, 20% and 17% respectively. The results of this study indicate that fluconazole provides benefit for the therapy of seborrheic dermatitis. However, larger studies using different dosages and durations of therapy, fluconazole may provide a rationale for systemic use of fluconazole in seborrheic dermatitis. DOI: http://dx.doi.org/10.3329/medtoday.v24i2.15009 Medicine Today 2012 Vol.24(2): 66-69